Tooth Loss In Elderly With Cognitive Function Based On Gender At Posyandu Elderly In Manggis Village, Panggul, Trenggalek District - Isnanto, Isnanto; Rohmah, Siti; Hidayati, Sri (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Tooth loss is one of the problems that often occurs in the elderly and has an adverse impact starting with a decrease in speech, chewing and decreased cognitive function. Impaired cognitive function of the elderly is due to difficulties in the process of chewing food, as well as the initial procedure for digesting it where there is an expulsion into a bolus to support the swallowing stage. Initial survey findings in August 2023 found a high percentage of the elderly population as much as (60%) of the elderly who have <20 teeth functioning at the Posyandu Lansia Desa Manggis, Panggul, Trenggalek Regency. This type of research is analytic quantitative observational. Using a survey method with a Cross Sectional approach. The population in this study were elderly people aged 60 years and over at the Manggis Village Elderly Posyandu, Panggul, Trenggalek Regency with a total of 40 elderly people. The data collection instruments used were MMSE questionnaire examination sheets and dental examination observation sheets. The data analysis technique used was the Spearmen correlation test. The results of this study are cognitive function based on gender has a normal cognitive function. The level of tooth loss in the elderly based on gender has a high category which means that the level of tooth loss in elderly men and women has a number of functioning teeth <20 teeth. The conclusion is that tooth loss is related to cognitive function in the elderly at Posyandu Lansia Desa Manggis, Panggul, Trenggalek Regency.Â